INTEGRATION OF MORAL PHILOSOPHY IN ENGLISH LANGUAGE LEARNING: AN ANALYSIS OF COMMUNICATIVE ETHICS TO BUILD THE CHARACTER OF PANCASILA THROUGH GROUP DISCUSSIONS - Karimatunnisa; Nurhayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study looks at how moral philosophy can be included in English learning through group discussions, which aim to help students develop good communication skills based on the values of Pancasila. The main focus is on how group discussions can help build civility, encourage fair participation in speech, and show respect for the dignity of others. These discussions do more than just teach language skills; They also help students understand and practice ethical communication during conversations. This research uses a qualitative approach with a case study method, and involves observing how students interact during discussions. Data is analyzed by grouping information and understanding the meaning behind what is said, based on moral values. The results show that adding moral philosophy to learning helps students become more aware of ethical behavior, reduces the tendency to dominate conversations, increases their willingness to listen, and makes them use more polite language. As a result, discussion becomes a place for equal and thoughtful communication, not just arguments. A unique part of this research is to create a teaching model that combines Pancasila values, ethical communication, and group discussion methods to help students become ethical speakers, not just good at speaking. The study also highlights the need for a set of rules for discussion ethics, a curriculum that includes moral and language aspects, and teachers who guide students to be fair, empathetic, and thoughtful in their communication. These findings suggest a new way of teaching English that focuses on using language to build character and humanity, not just on academic skills.